Prevention of deep vein thrombosis in patients with aneurysmal subarachnoid hemorrhage: a best practice implementation project - Wenguang Xie; Tingting Lu; Xinchen Yang; Yulu Deng; Shilin Liu; Shuyuan Huang; Wei Xiao; Chao Zhang; Yanyan Gong (BMC, 2024)
Abstract Introduction Deep vein thrombosis (DVT) is a common complication observed in aneurysmal subarachnoid hemorrhage (aSAH) patients, which significantly increases the survival risks and reduces the patient's quality of life. However, preventive clinical measures for DVT have not been standardized; therefore, the scientific basis and effectiveness of these measures require further validation. Objective This study aims to employ evidence-based practices to effectively prevent the occurrence of DVT in aSAH patients. Methods This study was performed from June 2023 to March 2024 in the neurosurgical intensive care unit of a Grade III Class A general hospital in Nanchang, China. Furthermore, it was based on the healthcare model published by the Joanna Briggs Institute Library (JBI) in 2016, which emphasizes the use of previous evidence-based practices while considering appropriateness, feasibility, clinical significance, and validity. In this research study, 15 review indicators were developed, and baseline assessments on 47 nurses and 49 patients were conducted. Furthermore, factors promoting and obstructing implementation were analyzed, and targeted strategies to address these obstacles were formulated. Moreover, a follow-up audit was performed to identify best practices. Results The baseline review results indicated that the incidence of DVT in aSAH patients was 16.3%. Furthermore, the implementation rates of six review indicators (1, 2, 4, 5, 8, 13) were all < 100.0%, with indicators 2, 5, and 8 indicating < 60.0% implementation rates. After the project implementation, a subsequent audit revealed that the best practice initiative yielded significant improvements compared to the baseline data. Moreover, the incidence of lower limb DVT in aSAH patients decreased from 16.3% before the evidence-based practices to 6.1% after their implementation. At the nursing level, the DVT prevention knowledge and practice questionnaire scores increased from 63.62 ± 11.48 to 74.77 ± 9.98 after the evidence-based practices (t = -5.03, p < .001). In addition, the implementation rates of the six review indicators improved to varying degrees after the implementation of evidence-based practices (p < .050). Conclusions This project implemented evidence-based practices and indicated a reduced incidence of lower limb DVT in patients with aSAH. Furthermore, this study improved the knowledge, provided evidence for DVT prevention for the neurosurgical ICU nurses, promoted the implementation rate of review indicators for DVT prevention, standardized the behavior of neurosurgical ICU nurses for preventing DVT in aSAH patients, and ensured the safety of patients. Trial registration This study has been registered at the EvidenceBased Nursing Center of Fudan University in China. Clinical trial number ER20230578.